From the internal market to a banking union: A proposal by the German Council of Economic Experts - Peter Bofinger; Claudia M. Buch; Lars P. Feld; Wolfgang Franz; Christoph M. Schmidt (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2012)
The European sovereign debt crisis has revealed severe flaws in the design of the internal market. Both, private and public borrowers had incentives for excessive borrowing, which have been created by deficits in the regulatory structure of financial markets. Capital requirements for banks were too low and had procyclical effects (Favara and Ratnovski 2012). Supervision has been ineffective with regard to containing the build-up of risks in banks' balance sheets. Common monetary policy in the Euro Area has not been accompanied by the transfer of authority to supervise and restructure banks which has, in turn, created incentives to shift risks to the European level. Risks of banks and states have become dangerously intertwined. Proposals for a banking union aim at correcting these deficits. In principle, a banking union is a necessary complement to other elements of the internal market. In an integrated capital market, banking distress in one country can have negative externalities for the stability of financial systems in other countries. Such risks are even more pronounced if other countries are affected through a common monetary policy. The banking union currently being discussed has three elements (President of the European Council 2012): banking supervision at the European level, a European authority for bank restructuring and resolution financed by a bank resolution fund, and a European deposit insurance fund. So far, concrete proposals have been made for the establishment of a Single Supervisory Mechanism only. However, a banking union is a long-term project. It is not the key to a solution to the acute problems in Europe's banking sectors (Buch and Weigert 2012, GCEE 2012a). – – Die europäische Schuldenkrise hat zentrale Defizite des Binnenmarkts offengelegt. Regulatorische Defizite haben Anreize geschaffen, eine zu hohe Verschuldung einzugehen. Zwar wurde eine einheitliche Geldpolitik verfolgt, gleichzeitig aber die Kompetenzen für die Aufsicht und Restrukturierung von Banken auf nationaler Ebene belassen. So sind Anreize entstanden, Risiken auf die europäische Ebene zu verlagern. Eine Bankenunion und die Etablierung eines einheitlichen Aufsichtsmechanismus haben das Ziel, diese Defizite zu beheben. Grundsätzlich ist eine Bankenunion eine notwendige Ergänzung des Binnenmarkts. Sie ist aber vor allem ein langfristiges Projekt, das keinesfalls das aktuelle Problem des privaten und öffentlichen Schuldenüberhangs lösen kann (Buch und Weigert, 2012; SVR, 2012a).
Keywords: 330